2017
DOI: 10.1016/j.segan.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

PMU-assisted overcurrent protection for distribution feeders employing Solid State Transformers

Abstract: Solid State Transformer (SST) has recently emerged as an approach to facilitate the integration of Distributed Energy Resources (DERs) at the distribution system level. However, SSTs impact the operation and coordination of protection relays as they will contribute to the fault current during a fault. This paper shows that the impact of SSTs on the overcurrent protection relays can be considerable. The paper proposes an enhancement to the traditional overcurrent scheme by exploiting embedded PMU functionality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…The locations of PMUs are: buses 2, 8, 11, 15, 17, 20, 24, 26, 30, 32. Considering the cost and state estimation accuracy comprehensively, the compromise solution is selected by TOPSIS. The compromise solution needs 11 PMUs, and the locations are buses 2,4,8,11,15,17,20,24,26,30,32. In order to reflect the influence of network compression on OPP, this paper uses the single variable method to compare two cases, the result of the comparison is shown in Table 1.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The locations of PMUs are: buses 2, 8, 11, 15, 17, 20, 24, 26, 30, 32. Considering the cost and state estimation accuracy comprehensively, the compromise solution is selected by TOPSIS. The compromise solution needs 11 PMUs, and the locations are buses 2,4,8,11,15,17,20,24,26,30,32. In order to reflect the influence of network compression on OPP, this paper uses the single variable method to compare two cases, the result of the comparison is shown in Table 1.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…where x (k+1) and x (k) are the state variable vectors obtained by the k − th and (k + 1) − th iterations respectively. Newton method is applied to solve the iterative Equations (8). The estimated state vectorx can be obtained when the convergence criterion is satisfied.…”
Section: The Basic Model Of State Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…2, it is quite limited with two-stage SST compared to the typical fault current with a two-level VSC that can potentially impact existing protection performance. For example, the research in [21] and [22] have concluded that the constraints on the SST's contribution to the fault current can have a significant impact on the operation and coordination of overcurrent relays. In response to this, a number of DC voltage-based protection methods have been proposed and developed by different researchers for protecting DC systems against limited prospective fault currents.…”
Section: Protection Challenges Of a Sst-interfaced Lvdc Distribution mentioning
confidence: 99%